Gene Expression and Control - Uchiumi, Fumiaki (IntechOpen, 2019)
Transcription is the most fundamental nuclear event, by which the information of nucleotide sequences on DNA is transcribed into RNA by multiple proteins, including RNA polymerases. Transcription determines the functions of proteins and the behaviour of cells, appropriately responding to environmental changes.This book is intended for scientists, especially those who are interested in the future prospect of gene expression and control in medicine and industry. This book consists of 9 chapters, divided into four parts. Each chapter is written by experts both in the basic and applied scientific field. A collection of articles presented by active and laboratory-based investigators provides evidence from the research, giving us a rigid platform to discuss "Gene Expression and Control."